2017
DOI: 10.1021/acs.jpca.7b07623
|View full text |Cite
|
Sign up to set email alerts
|

Triplet Excited State of BODIPY Accessed by Charge Recombination and Its Application in Triplet–Triplet Annihilation Upconversion

Abstract: The triplet excited state properties of two BODIPY phenothiazine dyads (BDP-1 and BDP-2) with different lengths of linker and orientations of the components were studied. The triplet state formation of BODIPY chromophore was achieved via photoinduced electron transfer (PET) and charge recombination (CR). BDP-1 has a longer linker between the phenothiazine and the BODIPY chromophore than BDP-2. Moreover, the two chromophores in BDP-2 assume a more orthogonal geometry both at the ground and in the first excited … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
137
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 104 publications
(143 citation statements)
references
References 67 publications
(135 reference statements)
6
137
0
Order By: Relevance
“…Up to now, only a limited number of molecular systems that are able to form triplet states through SOCT‐ISC have been analysed by TREPR . In particular, for the recently reported Bodipy‐derived electron donor/acceptor dyads showing SOCT‐ISC, TREPR spectroscopy has been rarely applied to confirm the ISC mechanism . Herein, we performed a detailed TREPR spectral study of the compact electron donor/acceptor dyads (Figure ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Up to now, only a limited number of molecular systems that are able to form triplet states through SOCT‐ISC have been analysed by TREPR . In particular, for the recently reported Bodipy‐derived electron donor/acceptor dyads showing SOCT‐ISC, TREPR spectroscopy has been rarely applied to confirm the ISC mechanism . Herein, we performed a detailed TREPR spectral study of the compact electron donor/acceptor dyads (Figure ).…”
Section: Resultsmentioning
confidence: 99%
“…In this regard, triplet PSs based on spin–orbit charge‐transfer ISC (SOCT‐ISC) have recently attracted much attention. It was found that for compact electron donor/acceptor dyads, ISC can be greatly enhanced given the electron donor and acceptor are in orthogonal geometry . The mechanism responsible for triplet generation in these systems is similar to the ISC involving nπ*↔ππ* transitions.…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…The 1,7‐methyl groups on the boron dipyrromethene (Bodipy) moiety play a similar role in Bodipy‐derived electron donor/acceptor dyads showing SOCT‐ISC . We found that the presence of peri ‐H(C) of electron donor phenothiazine is helpful for conformation restriction . However, in all these molecular structural motifs, rotation about the C−C or the C−N linker is not fully restricted, and various conformations are still accessible with thermal energy.…”
Section: Introductionmentioning
confidence: 97%